Identifying change processes in group-based health behaviour-change interventions: development of the mechanisms of action in group-based interventions (MAGI) framework. Issue 3 (3rd July 2019) - Borek, Aleksandra J.; Abraham, Charles; Greaves, Colin J.; Gillison, Fiona; Tarrant, Mark; Morgan-Trimmer, Sarah; McCabe, Rose; Smith, Jane R.
ABSTRACT: Group-based interventions are widely used to promote health-related behaviour change. While processes operating in groups have been extensively described, it remains unclear how behaviour change is generated in group-based health-related behaviour-change interventions. Understanding how such interventions facilitate change is important to guide intervention design and process evaluations. We employed a mixed-methods approach to identify, map and define change processes operating in group-based behaviour-change interventions. We reviewed multidisciplinary literature on group dynamics, taxonomies of change technique categories, and measures of group processes. Using weight-loss groups as an exemplar, we also reviewed qualitative studies of participants' experiences and coded transcripts of 38 group sessions from three weight-loss interventions. Finally, we consulted group participants, facilitators and researchers about our developing synthesis of findings. The resulting 'Mechanisms of Action in Group-based Interventions' (MAGI) framework comprises six overarching categories: (1) group intervention design features, (2) facilitation techniques, (3) group dynamic and development processes, (4) inter-personal change processes, (5) selective intra-personal change processes operating in groups, and (6) contextual influences. The framework provides theoretical explanations of how change occurs in group-based behaviour-change interventions and can be applied to optimise their design and delivery, and to guide evaluation, facilitator training and further research.